Studi Higiene Sanitasi Makanan Dengan Pemeriksaan Escherichia coli Air Pencucian dan Peralatan Makan Di Pujasera X - Yulianti Pratama; Nadya Almira Rachman (Jurnal Serambi Engineering, 2020)
Food sanitation is one of the methods used to protect food from contamination, maintain quality, and prevent potential bacterial transmission. This research was conducted to observe potential diseases caused by the microbiological quality of clean water for household use. MPN method was used to compare the quality of clean water based on the Peraturan Menteri Kesehatan Nomor 416 Tahun 1990. Swab method was implemented to observe the hygiene level of the cutlery to compare with the Peraturan Menteri Kesehatan Nomor 1098 Tahun 2003. 79/100 ml of total coliform found in tenant 1 and tenant 2 which means it did not meet the standards. Escherichia coli were found absent in both clean water sources. The same result comes from 2 samples of plates and spoons before and after the first usage and second usage. In tenant 2, Escherichia coli were found in plate sample no.1 before usage and the clerk’s hands before serving the food. Hence, it did not meet the standards. Based on the interviews and observations, the sanitation hygiene of the clerks and the physical hygiene of tenant 1 and tenant 2 had only fulfilled 61.9% and 57.1% of proper hygiene, so it needed to be improved.